ETIKA HAKIM DAN PENALARAN MORAL DALAM FILSAFAT HUKUM: TINJAUAN DEONTOLOGIS DAN UTILITARIAN TERHADAP KASUS HARVEY MOEIS - Rasji, Rasji; Akhir, Akhirudin (Journal of Business, Management, and Social Studies, 2025)
The purpose of this study is to explore the alignment between judicial decisions and ethical principles through the lens of legal philosophy, using the Harvey Moeis corruption case as a focal point. This research employs a descriptive qualitative method with juridical-normative and philosophical approaches. It involves the analysis of judicial decisions, legal norms, and ethical codes such as KEPPH, combined with theoretical frameworks from deontology, utilitarianism, and virtue ethics. The study finds that while the court’s decision attempted to uphold justice, concerns remain regarding judicial integrity and impartiality. The ruling emphasizes deterrence but reflects the need for stronger adherence to ethical and philosophical principles. This study contributes a philosophical-ethical analysis of a contemporary judicial case in Indonesia, highlighting the moral dimension of legal reasoning often overlooked in procedural legal analysis.